2020
DOI: 10.1111/aogs.13817
|View full text |Cite
|
Sign up to set email alerts
|

Levonorgestrel‐releasing intrauterine system and breast cancer risk: A systematic review and meta‐analysis

Abstract: IntroductionEpidemiological studies have shown that some hormonal contraceptive methods are associated with increased breast cancer risk, especially if used over long periods. Our objective was to conduct a systematic review and meta‐analysis of the literature on the risk of breast cancer development in women using the 52‐mg levonorgestrel‐releasing intrauterine system (LNG‐IUS).Material and methodsWe performed a thorough review of peer‐reviewed publications from 10 January 1999, through 31 July 2019, using co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
60
1
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(67 citation statements)
references
References 23 publications
1
60
1
5
Order By: Relevance
“…9,14,15 A recent meta-analysis of observational data suggests an increased risk in all users of the levonorgestrel intra-uterine system, which is greater in women over 50. 16 Risk may not be elevated if dydrogesterone or micronised progesterone is used in preference to synthetic progestogens, but further confirmatory evidence is needed; 13,14,17 Risk of diagnosis is not elevated in past users of HRT; 9 Risk is limited to lean women (i.e. not overweight or obese); 5 There does not appear to be a dosage effect; 15 There is no additive effect in women at elevated personal risk due to a family history or high-risk benign breast condition; 5,15 In women with premature ovarian insufficiency (POI), it is recommended that years of HRT exposure should be counted from the age of 50 and not at the age of HRT commencement when POI is diagnosed.…”
Section: Hrt and The Risk Of Being Diagnosed With Breast Cancer Studmentioning
confidence: 99%
See 1 more Smart Citation
“…9,14,15 A recent meta-analysis of observational data suggests an increased risk in all users of the levonorgestrel intra-uterine system, which is greater in women over 50. 16 Risk may not be elevated if dydrogesterone or micronised progesterone is used in preference to synthetic progestogens, but further confirmatory evidence is needed; 13,14,17 Risk of diagnosis is not elevated in past users of HRT; 9 Risk is limited to lean women (i.e. not overweight or obese); 5 There does not appear to be a dosage effect; 15 There is no additive effect in women at elevated personal risk due to a family history or high-risk benign breast condition; 5,15 In women with premature ovarian insufficiency (POI), it is recommended that years of HRT exposure should be counted from the age of 50 and not at the age of HRT commencement when POI is diagnosed.…”
Section: Hrt and The Risk Of Being Diagnosed With Breast Cancer Studmentioning
confidence: 99%
“…9,14,15 A recent meta-analysis of observational data suggests an increased risk in all users of the levonorgestrel intra-uterine system, which is greater in women over 50. 16 Risk may not be elevated if dydrogesterone or micronised progesterone is used in preference to synthetic progestogens, but further confirmatory evidence is needed; 13,14,17…”
Section: Hrt and The Risk Of Being Diagnosed With Breast Cancer Studmentioning
confidence: 99%
“…This is particularly important if the LNG-IUS is being used for endometrial protection rather than an established clinical indication, and should be a focus of future work. There is no evidence that the LNG-IUS increases the risk of cardiometabolic disorders in obese women [48], but a recent systematic review found LNG-IUS users have a modestly increased breast cancer risk (odds ratio =1.16 (95% CI 1.06-1.28, I2 =78%, p<0.01), although most of the included studies failed to adjust for BMI [49]. Clearly this is an important area for further research.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the localized release of the drug, blood serum levels of levonorgestrel are lower compared to other hormonal contraceptives, and ADRs were supposed to occur less pronounced or mainly in the initial months of use. However, an increased risk of breast cancer ( 2 ) and an emerging evidence regarding mood disorders and suicide attempts ( 3 6 ) arises the question of clinically relevant systemic and in particular psychotropic effects of LNG-IUS. Previous studies investigated ADRs only over a time period of 3 to 5 years after implantation ( 7 9 ).…”
Section: Introductionmentioning
confidence: 99%